Endplate changes after lumbar discectomy with and without implantation of an annular closure device - Barth, Martin; Weiß, Christel (Acta neurochirurgica, 2018)
The implantation of a bone-anchored annular closure device (ACD) might be associated with the developed new endplate changes (EPC) after surgery.
Gesehen am 12.08.2020